2010
DOI: 10.2527/jas.2010-2936
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different commercial phytase enzymes and development of an available phosphorus release curve for Escherichia coli-derived phytases in nursery pigs12

Abstract: In 2 experiments, a total of 184 pigs (PIC, initial BW of 10.3 and 9.7 kg for Exp. 1 and 2, respectively) were used to develop an available P (aP) release curve for commercially available Escherichia coli-derived phytases. In both experiments, pigs were fed a corn-soybean meal basal diet (0.06% aP) and 2 diets with added inorganic P (iP) from monocalcium phosphate (Exp. 1: 0.075 and 0.15% aP; Exp. 2: 0.07 and 0.14% aP) to develop a standard curve. In Exp. 1, 100, 175, 250, or 500 phytase units (FTU)/kg of Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
4
26
0
2
Order By: Relevance
“…4 Supplied per kilogram of diet: 60 mg of iron (ferrous sulfate); 120 mg of manganese (manganese sulfate and manganous oxide); 100 mg of zinc (zinc oxide); 1 mg of iodine (calcium iodate); 8 mg of copper (copper sulfate); 0.3 mg of selenium (sodium selenite). 5 Supplied per kilogram of diet: 9,600 IU of vitamin A; 3,600 IU of vitamin D 3 ; 18 mg of vitamin E; 15 µg of vitamin B 12 ; 10 mg of riboflavin; 48 mg of niacin; 18 mg of d-pantothenic acid; 2 mg of vitamin K; 1.2 mg of folic acid; 4 mg of vitamin B 6 ; 3 mg of thiamin; 72 µg of d-biotin. 6 Washed sand inclusion was variable depending on enzyme or formaldehyde-based additive diet inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Supplied per kilogram of diet: 60 mg of iron (ferrous sulfate); 120 mg of manganese (manganese sulfate and manganous oxide); 100 mg of zinc (zinc oxide); 1 mg of iodine (calcium iodate); 8 mg of copper (copper sulfate); 0.3 mg of selenium (sodium selenite). 5 Supplied per kilogram of diet: 9,600 IU of vitamin A; 3,600 IU of vitamin D 3 ; 18 mg of vitamin E; 15 µg of vitamin B 12 ; 10 mg of riboflavin; 48 mg of niacin; 18 mg of d-pantothenic acid; 2 mg of vitamin K; 1.2 mg of folic acid; 4 mg of vitamin B 6 ; 3 mg of thiamin; 72 µg of d-biotin. 6 Washed sand inclusion was variable depending on enzyme or formaldehyde-based additive diet inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Although not having a direct correlation with enzyme activity in vivo, and varying depending on the commercial product supplied, enzyme activity recovered in feed is often used as a direct comparison between different products [5]. Therefore, enzyme activity is often used for enzyme classification.…”
mentioning
confidence: 99%
“…It has been shown that the actual concentration of the product may be greater than the minimum guarantee (Sulabo et al, 2011). Second, it has been shown that there is large analytical variation associated with the laboratory assays utilized to measure phytase activity (Jones et al, 2010). In addition, the differences in the coating methods among the products may have inherently led to differences in assay results.…”
Section: Resultsmentioning
confidence: 99%
“…Beberapa hasil studi menunjukkan bahwa suplementasi fitase pada ransum dengan kandungan fosfor rendah menghasilkan pengaruh yang positif dalam meningkatkan kinerja pertumbuhan ayam pedaging (Ghazalah et al 2006;Singh 2008;Assuena et al 2009 1) Satu unit aktivitas fitase (FTU) didefinisikan sebagai jumlah enzim yang mampu membebaskan fosfor anorganik 1 μmol per menit dari larutan Na-fitat 0,0051 mol/l pada pH 5,5 dan suhu 37 o C (Jones et al 2010). …”
Section: Suplementasi Fitase Dalam Ransum Terhadap Kinerja Pertumbuhaunclassified